Alkhurma haemorrhagic fever virus causes lethal disease in IFNAR-/- mice - Bharti Bhatia; Elaine Haddock; Carl Shaia; Rebecca Rosenke; Kimberly Meade-White; Amanda J. Griffin; Andrea Marzi; Heinz Feldmann (Emerging Microbes and Infections)
Alkhurma haemorrhagic fever virus (AHFV), a tick-borne flavivirus closely related to Kyasanur Forest disease virus, is the causative agent of a severe, sometimes fatal haemorrhagic/encephalitic disease in humans. To date, there are no specific treatments or vaccines available to combat AHFV infections. A challenge for the development of countermeasures is the absence of a reliable AHFV animal disease model for efficacy testing. Here, we used mice lacking the type I interferon (IFN) receptor (IFNAR-/-). AHFV strains Zaki-2 and 2003 both caused uniform lethality in these mice after intraperitoneal injection, but strain 2003 seemed more virulent with a median lethal dose of 0.4 median tissue culture infectious doses (TCID50). Disease manifestation in this animal model was similar to case reports of severe human AHFV infections with early generalized signs leading to haemorrhagic and neurologic complications. AHFV infection resulted in early high viremia followed by high viral loads (<108 TCID50/g tissue) in all analyzed organs. Despite systemic viral replication, virus-induced pathology was mainly found in the spleen, lymph nodes, liver and heart. This uniformly lethal AHFV disease model will be instrumental for pathogenesis studies and countermeasure development against this neglected zoonotic pathogen.